The Wedge Strategy and China’s Response to the U.S.-ROK Semiconductor Alliance - Kejia Song; Yixin Li; Hao Wang (Chinese Journal of International Review)
In a world of digital transformation and intensified great power competition, semiconductors, as the core of Information Technology industry, a strategic and pioneering sector that supports the economic and social development of the country and safeguards national security, have become a determinant of a country’s comprehensive national strength. Naturally, the Biden administration identified the semiconductor as the key battlefield of the U.S.-China strategic competition, and set up a semiconductor alliance with its allies and partners to contain China’s technological innovation. As a vital country in the global semiconductor supply chain and a major U.S. allies, South Korea has become a contributor of the U.S. efforts. After Yoon Suk-Yeol came into power, the country has turned its diplomatic attention to the U.S. by not only helping form the semiconductor alliance but also upgrading the diplomatic ties between the two countries. Given that the U.S.-ROK semiconductor alliance would reshape China’s economic, technological and security environment from the outside, Beijing’s perception of and response to the alliance is a matter of concern. While existing studies on China’s perceptions of this semiconductor alliance are mainly based on realism of International Relations theory, this paper argues that liberalism with a core of economic interests, and neoclassical realism centered on domestic politics should also be taken into consideration. On this basis, this paper further refines the theoretical framework of the wedge strategy and uses it to analyze the reasons for and the effectiveness of China’s response to this alliance through both internal and external policies.